First record of pre‐settlement juvenile bluenose, Hyperoglyphe antarctica , from New Zealand - C. A. J. Duffy; A. L. Stewart; R. Yarrall (New Zealand Journal of Marine and Freshwater Research, 2000)
Epipelagic juvenile bluenose, Hyperoglyphe antarctica (Carmichael 1818), are recorded from New Zealand for the first time. Two specimens were collected beneath flotsam nearNga Motu/Sugar Loaf Islands, west coast North Island in September 1996, and at least 20 were found inside a piece of trawl net drifting east of Cape Kidnappers, east coast North Island in September 1997. Live specimens between 65 and 87.3 mm standard length were cryptically coloured and were able to change their body colour from dark coppery‐bronze to blue. Freshly dead specimens lacked the thick mucous coat found in juveniles of other Hyperoglyphe species known to associate with jellyfish. We suggest that H. antarctica recruitment may be higher along the lower east coast North Island because of retention of flotsam‐associated juveniles in the East Cape and Wairarapa Eddies, and that juveniles spawned off south‐east Australia may reach New Zealand in the Tasman Current.